ANALISIS PENGARUH JUMLAH ANGGOTA DAN JUMLAH PENYALURAN KREDIT TERHADAP JUMLAH SIMPANAN MASYARAKAT MELALUI CU DI KALIMANTAN BARAT - B61112035, VENERANDA RINI HAPSARI (Jurnal Ekonomi Daerah (JEDA), 2015)
ABSTRACT This study aims to identify and analyze the influence between the number of membersand the distribution towards the amount of savings in Credit Union, West Kalimantan. The research of method is using descriptive method. From the analysis it can be concluded that the independent variables such as the number of membersand the distribution, significantly influence on the amount of savings in West Kalimantan.The pattern of the relationship between the number of members, with the amount of savings is positive, the distribution of the savings with the amount of deposits is positively correlated. Moreover, the Hausman test results with Fixed Effect of each variable has a good value, so that, it can be concludedÂ that the amount of savings at Credit Union (CU) in West Kalimantan is greatly influenced by the independent variables that appears in this natural research. Keywords : The Number of Members, Distribution, The Amount of Savings and Credit Union